Endoscopic Evaluation of Upper Gastrointestinal Bleeding in Liver Cirrhosis - Kabir, Mohammad Rafiqul; Masud, Mahadi; Sharifunnesa; Karmaker, Partha Pratim; Arif, Mostafa; Talukder, Nazir Uddin; Islam, M M Shahin Ul (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Liver cirrhosis is a common, often progressive and usually fatal disorder. Upper gastrointestinal (UGI) bleeding is a leading cause of death in patient with cirrhosis. In this observational study, 50 patients were included according to selection criteria. Maximum participants (40%) were in the age group of 40-50 years of age (Mean ± SD = 42.94 ± 9.72, Minimum = 20 and Maximum = 62). Male were 68% and female were 32%. Male were more sufferer than female. Overall male to female ratio were 3:1. Esophageal varies was the commonest cause of haematemesis and melaena followed by portal hypertensive gastropathy, duodenal ulcer, gastric ulcer, erosive gastritis and reflux oesophagitis in patient with liver cirrhosis. Oesophageal varices were found in 60% participants. There were no gastric varices found among the participants. Presence of Portal HTN gastropathy was in 14% patients. Gastric ulcer was found in only 6% patients, 10% patients had duodenal ulcer, 3 (6%) patients had reflux oesophagitis, erosive gastritis was also present in 3(6%) of participants. Haematemesis, melaena and both haematemesis and melaena were noted in 24%, 22% and 54% of the patients respectively. HBsAg was positive in 50% patient. HCV was positive among 18% patients. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):74-78